Perbedaan Sick Building Syndrome Antara Rumah Beratap Asbes dan Rumah Beratap Genteng di Perumahan Giri Satria Permai, Kaliwatubumi, Butuh, Purworejo - Ika Ermaningsih; Siti HanI Istiqomah; Sigid Sudaryanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2010)
Asbestos has been proved not good for health and environment, so that the material is not advised to be used for housing. The exposure of asbestos in dwelling can lead to sick building syndrome (SBS), which consists of several symptoms such as headache, eye irritation, fever, dyspnea, cough, sneeze, and skin iritation. The study was aimed to understand the difference of getting SBS between tiled-roof houses and asbestos-roof houses at Giri Satria Permai Housing in Butuh, Purworejo Regency. The study was a cross sectional survey with restrospective approach. The incidence of SBS was collected du-ring the last three months for dwellers aged 10 years or more. There were 15 houses for each type of roof. The study shows that the number of SBS inci-dence was significantly higher in asbestos-roofed house; and descriptively the worse the roof condition the higher the number of the incidence. It suggested that the dwellers who live in asbestos-roff houses to install ceiling as a barrier for asbestos exposure.